POLA DOA ORANG PERCAYA BERDASARKAN MATIUS 6:9-13 dan LUKAS 11:2-4 - Jundo P. Siregar; Alon Mandimpu Nainggolan (Program Studi Teologi, Fakultas Teologi, Institut Agama Kristen Negeri Manado, 2023)
Praying is the obligation of every believer because it is commanded by God himself. God hears, and this assures believers not to give up praying. This paper uses a qualitative descriptive method by exploring the prayer taught by the Lord Jesus in Matthew 6:9-13 and Luke 11:1-4. As a result, there is the concept of a believer's prayer, which states the relationship between God and man. There is a prayer pattern in the prayer taught by the Lord Jesus, namely a balance of requests for the needs of God and His honor and requests for the physical, psychological, and spiritual needs of humans. Ended by acknowledging the glory of the Lord God, Amen.